Effect of increasing densities of Urochloa brizantha cv. Marandu on Eucalyptus urograndis initial development in silvopastoral system - Colmanetti, Michel Anderson Almeida; Bacha, Allan Lopes [UNESP]; da Costa Aguiar Alves, Pedro Luis [UNESP]; de Paula, Rinaldo Cesar [UNESP] (Springer Nature, 2018)
In silvopasture system, the coexistence of eucalyptus seedlings with other species may result in growth reduction, especially during eucalyptus early development. Therefore, studies elucidating how forage species affect the eucalyptus growth can provide important information for their rational management aiming to obtain the maximum gain of the system. The aim of this work was to evaluate the effect of increasing densities of Urochloa brizantha cv. Marandu in the early development of Eucalyptus urograndis. An experiment was conducted in 20 L pots, in an open and semi-controlled area, during 90 days after planting of eucalyptus. A completely randomized design with four replications was used, in a 6 × 7 factorial system, meaning six evaluation periods and seven densities of U. brizantha: 0 (control), 22, 33, 44, 67, 89 and 111 plants m−2. Fortnightly, eucalyptus height, stem diameter and chlorophyll fluorescence (Fv/Fm) were evaluated. At the end of experimental period, the net assimilation rate, stomatal conductance and transpiration rate of eucalyptus plants were determined, in addition to the dry matter of eucalyptus (leaves and stem) and U. brizantha (leaves). In coexistence with 111 plants m−2, eucalyptus had reduction of 63.9% on total dry matter and 72.7% on leaf area, compared to the control. From the density of 22 plants m−2, U. brizantha negatively interfere significantly the growth of E. urograndis. Up to 8 plants m−2 there are no reductions greater than 5% in eucalyptus height and stem diameter.
Keywords: Competition; Eucalyptus; Interference; Palisade grass